Climate indicators for agriculture - Walsh, Margaret K., author; Backlund, Peter W., author; Buja, Lawrence, author; DeGaetano, Arthur, author; Melnick, Rachel, author; Prokopy, Linda, author; Takle, Eugene, author; Todey, Dennis, author; Ziska, Louis, author (Colorado State University. Libraries, 2020)
Climate Indicators for Agriculture identifies 20 climate indicators that are important for agricultural management in a changing climate. The same indicators will allow scientists to identify the types and magnitude of change faced by agricultural producers and land managers across the United States. Five categories of indicator are described. Physical indicators show changes in climate variables that have direct effects on agricultural production and food systems. Crop and Livestock indicators show climate-induced changes in agricultural systems. Biological Indicators show how climate change is altering the range and infestation intensities of weeds, pests, disease and disease vectors that affect crop production and animal agriculture. Phenological Indicators show how climate change is affecting the timing of seasonal activities in agriculture, such as the date of flowering and pollination for a given crop. Socioeconomic Indicators show how human and economic factors in agriculture are affected by climate change.
Keywords: climate change; climate impacts; agriculture